SISTEM PRESENSI GURU DAN PEGAWAI BERBASIS PENGENALAN WAJAH MENGGUNAKAN ALGORITMA VIOLA-JONES DAN LOCAL BINARY PATTERN HISTOGRAMS - Kembuan, Olivia; Wuntu, Lucky; Rantung, Vivi (Program Studi Teknik Informatika, 2025)
The process of collecting data on the attendance of teachers and employees at GMIM 2 Tondano Elementary School still uses manual methods and has not been computerized both in taking attendance data to the process of recapitulating attendance data. Based on this, this research aims to design and develop an attendance system by applying face recognition technology. An agile software development method with scrum framework is used to develop the system, this system uses the Viola-Jones algorithm to perform face detection, and uses the Local Binary Pattern Histogram (LBPH) algorithm for face recognition. With a test distance of 1 meter the ViolaJones algorithm gets an accuracy result of 100% and for a distance of 2 meters gets an accuracy result of 0%. Local Binary Pattern Histograms (LBPH) algorithm, getting 100% accuracy for 40 tests with 4 different face samples with a testing distance of 1 meter between the camera and the faces. Based on the results of the tests, it can be concluded that the face recognition-based attendance system was successfully developed for use by teachers and employees at GMIM 2 Tondano Elementary School.